Desaturation-Induced Brightness in Face Color Perception. (June 2019) - Shimakura, Hitomi; Sakata, Katsuaki
The distinctiveness of perception of face from nonface objects has been noted previously. However, face brightness is often confounded with whiteness in the beauty industry; few studies have examined these perceptual differences. To investigate the interactions among face color attributes, we measured the effect of saturation on brightness and whiteness in both uniform color patches and face images to elucidate the relationship between these two perceptions. We found that, at constant luminance, a uniform color patch looked brighter with an increase in saturation (i.e., the Helmholtz–Kohlrausch effect occurred), while in contrast, brightness of a facial skin image looked less bright with increased saturation (i.e., contrary to the Helmholtz–Kohlrausch effect), which suggested this interaction of color attributes was influenced by top-down information. We conclude that this inverse effect of saturation on brightness for face images is not due to face recognition, color range of the skin tone, the luminance distribution, or recognition of human skin but due to the composite interactions of these facial skin factors in higher order recognition mechanisms.